Prognostic role of the systemic immune-inflammation in patients with non-small cell lung cancer: a meta-analysis - Zhao, Guomin; Zhang, Hui; Ye, Pucong; Chen, Wei (Journal of the Pakistan Medical Association, 2026)
Objective: To explore the prognostic value of systemic immune-inflammation in assessing patients with non-small cell lung cancer. Method: The meta-analysis was conducted from May to July 2023, and comprised a comprehensive search PubMed, Excerpta Medica Database and Cochrane Library databases up to March 21, 2023, for relevant peer-reviewed articles evaluating the prognostic value of systemic immune-inflammation in patients with non-small cell lung cancer. Hazard ratio and 95% confidence interval were calculated to assess systemic immune-inflammation’s relationship with overall survival and progression-free survival. Data was analysed using STATA 17.0. Results: Of the 135 studies initially identified, 32(23.7%) were analysed in detail, involving 12,040 patients. Increased systemic immune-inflammation was significantly associated with poor overall survival (hazard ratio: 1.31; 95% confidence interval: 1.21-1.41; p<0.001) and progression-free survival (hazard ratio: 1.48; 95% confidence interval: 1.12-1.94; p<0.001) in non-small cell lung cancer patients. Subgroup analysis confirmed these findings, with significant associations observed across various subgroups (country, sample size, cut-off value, survival analysis type, and TNM stage). Sensitivity analysis showed that the pooled hazard ratios remained stable, with no significant changes upon the exclusion of individual studies (p=0.75 for OS and p=0.83 for PFS). Publication bias was assessed and no significant bias was observed for either OS or PFS (Egger’s test p=0.12 for OS and p=0.18 for PFS). Conclusions: High systemic immune-inflammation was found to be a significant predictor of poor overall survival and progression-free survival in non-small cell lung cancer patients. Key Words: Systemic immune-inflammation index, Non-small cell lung cancer, Meta-analysis, Prognosis.